The Battle Lines of Sexual Politics and Medical Morality - Lantos, John D. (The Hastings Center report, 2013)
One of two commentaries on “Normalizing Atypical Genitalia: How a Heated Debate Went Astray,” by Josephine Johnston, from the November-December 2012 issue.